A new thermo-mechanical approach to predict "burn-through" during the in-service welding. (15th December 2021) - Majnoun, Peyman; Ghavi, Mohammad Reza; Vakili-Tahami, Farid; Adibeig, Mohammad Reza
Abstract: Burn-through is one of the major concerns in the industry when carrying out in-service welding. For this reason, a new thermo-mechanical model is developed to calculate the temperature and stress distribution in the weldment of a T-shape pipe joint. Experimental data is used to validate the model. The results of the in-service welding simulation reveal that the currently used Battle's criterion is not safe enough for predicting burn-through, because it does not take into account the thermo-mechanical stresses. Also, results show that there are some cases with a high risk of burn-through despite satisfying Battelle's criterion, whereas, the new model is capable to identify these cases. If it is difficult to use this new model in the industrial environment, it is recommended to use Battelle's criterion with lower threshold temperature (800 ° C instead of 982 ° C ) especially for alloys with low thermal conductivity and those with a low ultimate tensile strength at high temperatures. Highlights: A new criterion is proposed to assess the possibility of burn-through during the in-service welding. It takes into account the effects of both thermo-mechanical stresses and temperature distribution in the weldment. An experimental rig is designed to measure the induced temperature distribution and residual stresses caused by the in-service welding. Numerical simulations have been carried out to model the in-service welding and the results are compared with the measured experimental data and good agreement has been observed. A new parameter known as "remaining thickness (t*)" is introduced to assess the ability of the weldment to identify the possibility of burn-through.